An Analysis of Students’ Speaking Performance Difficulties in Video Task at 8th Grade of SMPN 3 Ampek Angkek - Muhammad Abdillah; Syahrul Syahrul; Irwandi Irwandi; Widya Syafitri (Austronesian: Journal of Language Science & Literature, 2026)
Student video-based tasks have become an essential medium in language learning, particularly in improving students’ speaking performance, as they provide opportunities to practice pronunciation, fluency, and confidence through recording, reviewing, and refining speech. Despite these benefits, preliminary research at SMPN 3 Ampek Angkek revealed that many students experienced difficulties when completing video-based speaking tasks, including pronunciation errors, low confidence, nervousness, and lack of fluency. Some students appeared hesitant, avoided eye contact, spoke in a low tone, and struggled with articulation and clarity. This study employed a qualitative research design to explore these problems in depth, using observations and structured interviews as data collection methods. The data were obtained from students’ video assignments and interviews with students who experienced speaking difficulties. The findings indicated that three main factors contributed to students’ speaking problems: inhibition, nothing to say, and mother tongue interference. Inhibition was reflected in students’ anxiety, fear of making mistakes, and lack of self-confidence, which caused them to limit their speech and hesitate while speaking. The “nothing to say” factor was evident in students’ limited vocabulary mastery and insufficient understanding of the given topics, resulting in frequent pauses and disrupted fluency. Meanwhile, mother tongue interference negatively affected students’ pronunciation and sentence patterns and led to frequent code-switching between English and their first language. These findings suggest that teachers need to provide more structured speaking practice, strengthen students’ vocabulary and topic comprehension, apply confidence-building strategies, and offer focused pronunciation training to improve students’ speaking performance in video-based speaking tasks.